Effect of drinking water salinity on lactating cows’ water and feed intake, milk yield, and rumen physiology - A. Iritz; D. Espinoza; M.G. Taye; F. Salhab; Y. Portnik; U. Moallem; Y.A. Ben Meir (Animal)
Use of desalinated seawater in arid and semiarid regions for domestic, industrial, and agricultural purposes is on the rise. Consequently, in those regions, drinking water offered to lactating cows has lower salinity and mineral concentrations than in the past. Although water with total dissolved solids (TDSs) of up to 1 000 ppm is considered safe for drinking, lower salinity level may affect rumen physiology, feed and water intake, or milk yield. Therefore, we evaluated the effect of drinking water salinity in an electrical conductivity (EC) range of 400 to 1 000 micro Siemens (µS) / cm (TDS of 200 to 500 ppm) on lactating cows’ performance by artificially creating water EC > 400 µS/cm by adding NaCl. Following 2 weeks of adaptation to individual feeders and troughs, four Israeli Holstein multiparous lactating cows were offered, in a Latin square design, drinking water with EC levels of 400, 600, 800 or 1 000 µS/cm, through addition of concentrated NaCl solutions (measured EC in troughs averaged 418, 624, 811, and 1 016 µS/cm and 209, 312, 406, and 508 TDS ppm, respectively), for four periods of 18 days each. Water EC in troughs was measured daily. Each period included 5 days for washout, 10 days for collecting data of feed and water intake, milk and milk component yields, and BW and 3 days for samplings of milk, urine, faeces, and rumen fluid. Rumen pH and temperature were recorded continually by inserting loggers into the reticulorumen. We analysed the total tract apparent digestibility, rumen fluid volatile fatty acids and NH3, and mineral concentrations (Na, Cl, K, and N) in water, urine, faeces, and milk. Drinking water salinity was positively correlated with DM intake and energy-corrected milk yield, the latter showing the greatest response between EC of 400 and 600 µS/cm. Digestibility of ash-free amylase-treated NDF was negatively correlated with water salinity. There was no significant effect of water EC on rumen volatile fatty acid or NH3 concentrations, or water intake. The results indicate possible effects of drinking water mineral concentrations on lactating cows’ milk yield and rumen physiology, warranting further investigation.